MRI visibility of gold fiducial markers for image-guided radiotherapy of rectal cancer. (March 2019) - van den Ende, Roy P.J.; Rigter, Lisanne S.; Kerkhof, Ellen M.; van Persijn van Meerten, Els L.; Rijkmans, Eva C.; Lambregts, Doenja M.J.; van Triest, Baukelien; van Leerdam, Monique E.; Staring, Marius; Marijnen, Corrie A.M.; van der Heide, Uulke A.
Highlights: Gold Anchor and Visicoil 0.75 fiducials were the most consistently identified. Using a corresponding CT or CBCT improves fiducial detection on MRI. The use of a T1 3D GRE MRI sequence for fiducial detection is recommended. Abstract: Background and purpose: A GTV boost is suggested to result in higher complete response rates in rectal cancer patients, which is attractive for organ preservation. Fiducials may offer GTV position verification on (CB)CT, if the fiducial-GTV spatial relationship can be accurately defined on MRI. The study aim was to evaluate the MRI visibility of fiducials inserted in the rectum. Materials and methods: We tested four fiducial types (two Visicoil types, Cook and Gold Anchor), inserted in five patients each. Four observers identified fiducial locations on two MRI exams per patient in two scenarios: without (scenario A) and with (scenario B) (CB)CT available. A fiducial was defined to be consistently identified if 3 out of 4 observers labeled that fiducial at the same position on MRI. Fiducial visibility was scored on an axial and sagittal T2-TSE sequence and a T1 3D GRE sequence. Results: Fiducial identification was poor in scenario A for all fiducial types. The Visicoil 0.75 and Gold Anchor were the most consistently identified fiducials in scenario B with 7 out of 9 and 8 out of 11 consistently identified fiducials in the first MRI exam and 2 out of 7 and 5 out of 10 in the second MRI exam, respectively. The consistently identified Visicoil 0.75 and Gold Anchor fiducials were best visible on the T1 3D GRE sequence. Conclusion: The Visicoil 0.75 and Gold Anchor fiducials were the most visible fiducials on MRI as they were most consistently identified. The use of a registered (CB)CT and a T1 3D GRE MRI sequence is recommended.